British Thoracic Society Sarcoidosis study: effects of long term corticosteroid treatment. Issue 3 (March 1996) - Gibson, G J; Prescott, R J; Muers, M F; Middleton, W G; Mitchell, D N; Connolly, C K; Harrison, B D
Abstract : BACKGROUND: Corticosteroids suppress disease activity in pulmonary sarcoidosis and their use produces symptomatic, radiographic, and functional improvement. There is, however, uncertainty regarding their effects on the overall natural history of the condition and long term benefit is unproven. METHODS: Patients with pulmonary radiographic shadowing due to sarcoidosis were recruited in a multicentre study. Those who, in the first six months after entry to the study, neither required prednisolone for symptoms nor showed radiographic improvement were allocated at six months to receive either long term steroid treatment (group L) or selective treatment (group S), with regular assessment over the subsequent five years. Patients in group L were scheduled to receive steroid treatment for at least 18 months with the policy of achieving and maintaining maximal radiographic clearing, while in group S treatment was reserved for use only if warranted by later development of symptoms or deteriorating lung function. Symptoms, radiographic appearances, and respiratory function were assessed periodically during the study. RESULTS: One hundred and forty nine patients were followed: 33 required prednisolone for troublesome symptoms within six months of entry and 58 showed radiographic improvement over this period. The remaining 58 patients were allocated to groups L (n = 27) and S (n = 31). Patients in group L showed greater improvements in symptoms, respiratory function, and radiographic appearances than those in group S, although the differences were not large. After adjusting for differences at the time of allocation, the average difference in vital capacity between groups L and S at final assessment was 9% of the predicted value. Side effects of treatment were frequent but usually mild, necessitating withdrawal in only two individuals. CONCLUSIONS: After excluding those individuals who required steroids for control of symptoms, approximately half of the remaining patients with sarcoidosis and pulmonary shadowing showed spontaneous radiographic improvement during six months of observation. In those in whom the radiograph failed to improve, prolonged steroid treatment with the aim of optimising radiographic appearances resulted in a significantly better long term functional outcome.